Exploring Coupled Martensitic and Order–Disorder Phase Transitions in Fe7Pd3 Shape Memory Alloys Equilibrated Along the Bain Path: An Embedded Atom Method and Ab Initio Based Monte Carlo Study. Issue 3 (20th January 2022) - Holm, Alexander; Schmalfuß, Jonathan; Mayr, Stefan G.
Abstract: The ferromagnetic shape memory alloy, Fe7 Pd3, not only offers promising applications, but also reveals a number of unresolved scientific questions, including coupling between a series of martensite and order–disorder transitions, which are in the focus of the present study. To address and understand these aspects, which are of particular importance for controlling phase stability in Fe 7 Pd 3 Fe_7Pd_3, an ab initio based Monte Carlo simulation code is developed, whose results demonstrate that equilibrated ordered or disordered phases show distinct dependencies coupled to temperature and lattice structure. Moreover, in equiatomic domains emerging from initially randomized disorder, an intermediate, entropy stabilized phase is identified with significantly higher magnetic anisotropy energy, being advantageous for miniaturized applications. This phase, among other observed configurations, is comprehensively characterized by free energy landscapes and magneto‐structural coupling derived from vibrational analysis of molecular dynamics trajectories and full relativistic spin polarized density functional theory ground state calculations, respectively. Abstract : The coupled martensitic and order–disorder phase transitions in Fe7 Pd3 shape memory alloys are studied based on a self implemented Monte Carlo simulation code. A particular ordered phase is identified with a higher magnetic anisotropy energy compared to closely related equiatomic phases, which are relevant for advanced miniaturized applications.